2014
DOI: 10.1021/ef5021632
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation of Bulk Organic Matter in Type II Shales in the Middle of the Oil Formation Window

Abstract: In this work, we use molecular simulations to determine the structural and physical properties of the organic matter present in type II shales in the middle of the oil generation window. The construction of molecular models of organic matter constrained by experimental data is discussed. Using a realistic molecular model of organic matter, we generate, by molecular dynamics simulations, structures that mimic bulk organic matter under typical reservoir conditions. Consistent results on density, diffusion, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
149
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(162 citation statements)
references
References 60 publications
13
149
0
Order By: Relevance
“…11. It is evident that the pore diameter of the kerogen sample spans from a few Å to $14 Å, consistent with the simulation results reported by Collell et al [68]. To estimate the diffusion coefficient of n-octane through the disordered kerogen, we used grand canonical Monte Carlo (GCMC) simulations to generate initial structure of MD simulations.…”
Section: Effect Of Disordered Structuresupporting
confidence: 77%
See 2 more Smart Citations
“…11. It is evident that the pore diameter of the kerogen sample spans from a few Å to $14 Å, consistent with the simulation results reported by Collell et al [68]. To estimate the diffusion coefficient of n-octane through the disordered kerogen, we used grand canonical Monte Carlo (GCMC) simulations to generate initial structure of MD simulations.…”
Section: Effect Of Disordered Structuresupporting
confidence: 77%
“…Recent molecular simulation shows that kerogen density, specific adsorption, and other properties estimated from their model are consistent with the experimental data [68]. Here, we focus on the type II-C kerogen unit (Fig.…”
Section: Effect Of Disordered Structuresupporting
confidence: 75%
See 1 more Smart Citation
“…At the same time, using the Extended Langmuir model and Ideal Adsorbed Solution (IAS) model to fit the experimental results, Collell found that the predicted results of the two models were consistent with the simulation results under low pressure conditions, but at high pressure, only a small part of the predicted results was in agreement with the simulation results, and the smaller the pores, the worse the match between the properties became [47]. In the same year, based on the experimental data, Collell used the molecular simulation method to obtain the molecular structure and the physical properties of shale organics and obtained the stable kerogen molecular structure by molecular dynamics simulation [48]. Based on the C/H and C/O ration of I, II and III kerogen, Ungerer et al applied a molecular simulation method to establish a molecular structure model.…”
Section: Introductionsupporting
confidence: 70%
“…Zhang and LeBoeuf constructed molecules for Green River Shale kerogen and calculated the density and thermal expansion coefficient by MD [37]. Collell et al provided new models for type II kerogen and analyzed the micropore structure for the solid [9]. Bousige et al proposed a general kerogen molecule reconstruction method based on the carbon-carbon pair distribution function for all types of kerogen [5].…”
Section: Introductionmentioning
confidence: 99%